FACTORS ASSOCIATED WITH PRACTICES TOWARDS WATER, SANITATION AND HYGIENE WITH OCCURRENCE OF DIARRHOEA AMONG PUPILS IN SCHOOLS WITH A FEEDING PROGRAMME IN GANZE SUB COUNTY, KENYA - Mwai, Judy; Mwandawiro, C; Mutai, Dr. Joseph; Karanja, Prof. Simon; Karani, Prof. George (Journal of Health, Medicine and Nursing, 2020)
Purpose: Inadequate sanitation is a major factor that causes diarrhea in school-aged children, this leads to a number of health problems, including stunted growth, diarrheal illness and even death. The main objective of the study was to determine the factors associated with practices towards water, sanitation and hygiene with occurrence of diarrhoea among pupils in schools with a feeding programme in Ganze sub county, Kenya Methodology: A school-based cross-sectional study design was employed where 24 schools were sampled. 10 pupils were targeted from each school (240). Data was collected through a pre-tested structured questionnaire and keyed-into the SPSS and analysed. Results: Study findings indicate that majority of the pupils aged between 10 - 14 years were 69.7%, while those aged between 15-18years were 25.5% and the least was aged between 5-9 years old at 5.0%. Majority of the pupils were in class 5-6 forming 48.7% of the responses, followed by classes 7-8 at 46.7% while classes 3-4 at 4.6 %. The study results indicate that 54% of the pupils were female and 46% male. It was noted that there is statistical significance among pupils who had suffered from diarrhea (P>0.005). Gender (p<0.005), training on health related issues at school (P<0.005), as well as schools with Home Grown School Meals Programme (P<0.005) and Knowledge of diseases associated with WASH (Ï‡2= 108.519, df = 1, P<0.005) had a significance association with diarrhoea occurrence. Toilet usage (Ï‡2= 2.088, df = 1, P>0.005), availability of water (Ï‡2= 0.836, df = 2, P>0.005), availability of handwashing facilities (Ï‡2= 0.141, df = 1, P>0.005) had no significant association with occurrence of diarrhea. Further significance was noted on demographic (Î² = 0.867, P=.000) behavioural (Î² = 0.924, P=.000), environmental factors (Î² = 0.689, P=.000) and diarrhoea occurrence. Conclusions: Study indicates that environmental, demographic and behavioral factors significantly predict diarrhea occurrence. WASH related diseases, Trainings on WASH and implementation of HGSMP have a positive relationship with occurrence, prevention and control of diarrhea. Control programs should adopt a more comprehensive approach. School and community-based health education is also imperative to significantly reduce the spread and morbidity from diarrhoea.